I did try that,

As far as the model is concerned, it didn’t change anything, I’m still getting those residuals.

I tried to write a solver to find the starting value of all k, I tried by hand and it ended up being too much RAM for my brain, as I have problems with the timing of the choices.

I then tried to write a solver and it doesn’t work because I end up having Ct* in Ct expression and I can’t seem to find a way to reduce the entire expression. I thought the solver would end up able to solve it, but I must have made a mistake.

Here’s the solver code, maybe thats where my mistake is.

"clear

clc

x0 = [0.1;0.1;0.1;0.1;0.1;0.1;0.1;0.1];

solution = fsolve(@sol,x0)

function f = sol(x)

kt1 = x(1);

kt1 = x(2);

knt1 = x(3);

knt1 = x(4);

kst1 = x(5);

kst1 = x(6);

ksnt = x(7);

knst = x(8);

kt0 = 1 ;

knt0 = 1;

kst0 = 1;

knst0 = 1;

delta = 0.1;

beta = 0.96;

f1 = ((((((((kt0)^(.4))+((kst0)^(.4)) - Cts - ((kt1 - (.9)*(kt0))))^(1-2.5)) - ((kst1 - (.9)*(kst0))^(1-(2.5)) + ((((knt0)^(.4))-(knt1 - (0.9)*(knt0)))^(1-2.5)))))^(3.866666667))/((kt0)^(.4))+((kst0)^(.4)) - Cts - ((kt1 - (.9)*(kt0))-((kst1 - (.9)*kst0))^(2.5))) * 0.4/((kt0)^(0.6)) + (0.9);*

f2 = 0.96((((((((kt1)^(.4))+((kst1)^(.4)) - Cts - ((kt2 - (.9)*kt1)))^(1-2.5)) - ((kst2 - (.9)*(kst1))^(1-(2.5)) + ((((knt1)^(.4))-(knt2 - (0.9)*(knt1)))^(1-2.5)))))^(3.866666667))/((kt1)^(.4))+((kst1)^(.4)) - Cts - ((kt2 - (.9)**kt1)-((kst2 - (.9)**kst1))^(1-2.5))) * 0.4/((kt1)^(0.6)) + (0.9) - 1;*

f3 = ((((((((kt0)^(.4))+((kst0)^(.4)) - Cts - ((kt1 - (.9)(kt0))))^(1-2.5)) - ((kst1 - (.9)(kst0))^(1-(2.5)) + ((((knt0)^(.4))-(knt1 - (0.9)(knt0)))^(1-2.5)))))^(3.866666667))/((((knt0)^(.4))-((knt1 - (0.9)*(knt0)))^(2.5)))* ((0.4)/((knt0)^(.6)))+(0.9));

f4 = 0.96*((((((((kt1)^(.4))+((kst1)^(.4)) - Cts - ((kt2 - (.9)*(kt1))))^(1-2.5)) - ((kst2 - (.9)*(kst1))^(1-(2.5)) + ((((knt1)^(.4))-(knt2 - (0.9)*(knt1)))^(1-2.5)))))^(3.866666667))/((((knt1)^(.4))-((knt2 - (0.9)*(knt1)))^(2.5)))* ((0.4)/((knt1)^(.6)))+(0.9)) -1 ;

f5 = ((((((((kt0)^(.4))+((kst0)^(.4)) - Ct - ((kt1 - (.9)*(kt0))))^(1-2.5)) - ((kst1 - (.9)*(kst0))^(1-(2.5)) + ((((ksnt0)^(.4))-(ksnt1 - (0.9)*(ksnt0)))^(1-2.5)))))^(3.866666667))/((kt0)^(.4))+((kst0)^(.4)) - Ct - ((kt1 - (.9)*(kt0))-((kst1 - (.9)*kst0))^(2.5))) * 0.4/((kst0)^(0.6)) + (0.9);*

f6 = 0.96((((((((kt1)^(.4))+((kst1)^(.4)) - Ct - ((kt2 - (.9)*(kt1))))^(1-2.5)) - ((kst2 - (.9)*(kst1))^(1-(2.5)) + ((((ksnt1)^(.4))-(ksnt2 - (0.9)*(ksnt1)))^(1-2.5)))))^(3.866666667))/((kt1)^(.4))+((kst1)^(.4)) - Ct - ((kt2 - (.9)*(kt1))-((kst2 - (.9)*kst1))^(2.5))) * 0.4/((kst1)^(0.6)) + (0.9) -1 ;*

f7 = ((((((((kt0)^(.4))+((kst0)^(.4)) - Cts - ((kt1 - (.9)(kt0))))^(1-2.5)) - ((kst1 - (.9)*(kst0))^(1-(2.5)) + ((((ksnt0)^(.4))-(ksnt1 - (0.9)*(ksnt0)))^(1-2.5)))))^(3.866666667))/((((ksnt0)^(.4))-((ksnt1 - (0.9)*(ksnt0)))^(2.5)))* ((0.4)/((ksnt0)^(.6)))+(0.9));

f8 = 0.96 * ((((((((kt1)^(.4))+((kst1)^(.4)) - Cts - ((kt2 - (.9)*(kt1))))^(1-2.5)) - ((kst2 - (.9)*(kst1))^(1-(2.5)) + ((((ksnt1)^(.4))-(ksnt2 - (0.9)*(ksnt1)))^(1-2.5)))))^(3.866666667))/((((ksnt1)^(.4))-((ksnt2 - (0.9)*(ksnt1)))^(2.5)))* ((0.4)/((ksnt1)^(.6)))+(0.9)) - 1; "

and the error codes :

end

Unrecognized function or variable ‘Cts’.

Error in solverIME>sol (line 27)

f1 = ((((((((kt0)^(.4))+((kst0)^(.4)) - Cts - ((kt1 - (.9)*(kt0))))^(1-2.5)) - ((kst1 - (.9)*(kst0))^(1-(2.5)) + ((((knt0)^(.4))-(knt1 -

(0.9)*(knt0)))^(1-2.5)))))^(3.866666667))/((kt0)^(.4))+((kst0)^(.4)) - Cts - ((kt1 - (.9)*(kt0))-((kst1 - (.9)*kst0))^(2.5))) * 0.4/((kt0)^(0.6)) + (0.9);

Error in fsolve (line 258)

fuser = feval(funfcn{3},x,varargin{:});

Error in solverIME (line 6)

solution = fsolve(@sol,x0)

Caused by:

Failure in initial objective function evaluation. FSOLVE cannot continue.

So I’m stuck at the fact that Ct is Xt + Xt* - Ct* - It - It* leading me to have a Ct* in my Ct equation and a Ct in my Ct* equation and I’m getting real stuck at that point.

Continuing on, trying by hand, always interested in your pointers.